2022
DOI: 10.3389/fonc.2022.822708
|View full text |Cite
|
Sign up to set email alerts
|

Improved Clinical Workflow for Whole-Body Patlak Parametric Imaging Using Two Short Dynamic Acquisitions

Abstract: ObjectiveWe sought to explore the feasibility of shorter acquisition times using two short dynamic scans for a multiparametric PET study and the influence of quantitative performance in shortened dynamic PET.MethodsTwenty-one patients underwent whole-body dynamic 18F-FDG PET/CT examinations on a PET/CT (Siemens Biograph Vision) with a total scan time of 75 min using continuous bed motion for Patlak multiparametric imaging. Two sets of Patlak multiparametric images were produced: the standard MRFDG and DVFDG im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In terms of image quality, our study found that the quality of Ki-30 min images is as good as that of Ki-65 min images by visual quality assessment. In a different setting by Wang et al, they compared the MR glu images of two-short-dynamic-scanning protocols (0-6 min + 60-75 min) and standard scanning protocols concluding that both protocols produced good-quality MR glu images with no visual distinction [ 21 ]. In addition, our study found that the number of lesions detected in the two image types is consistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of image quality, our study found that the quality of Ki-30 min images is as good as that of Ki-65 min images by visual quality assessment. In a different setting by Wang et al, they compared the MR glu images of two-short-dynamic-scanning protocols (0-6 min + 60-75 min) and standard scanning protocols concluding that both protocols produced good-quality MR glu images with no visual distinction [ 21 ]. In addition, our study found that the number of lesions detected in the two image types is consistent.…”
Section: Discussionmentioning
confidence: 99%
“…It often needs another plasma input function (IF), such as population-based IF (PBIF). However, it may introduce errors into the parametric analysis as it does not take into account the specificity of the individual IF [ 20 ]; (ii) two-short-dynamic-scanning, which requires two separate scans after 18 F-FDG injection, such as (0-6 min + 60-75 min) scans, (0-10 min + 55-60 min) scans, (0-10 min + 40-60 min) scan and two 5-min scans [ 21 25 ]. These studies showed that the generated parameter metabolic rate of glucose (MR glu ) [ 21 ] or Ki [ 22 , 24 , 25 ] is highly correlated with the reference parameter calculated from the full scan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dias et al ( 9 ) recommended the use of a population-based input function (PBIF) to transform Patlak imaging into a 20-min procedure]. We have previously reported on the feasibility of shorter acquisition times using two short dynamic scans for a multiparametric PET study and the influence of quantitative performance in shortened dynamic PET ( 10 ). Several reports have demonstrated the use of dynamic whole-body PET/CT to describe parameters in normal tissues and different types of tumors, such as non-small cell lung cancer, breast cancer, nasopharyngeal carcinoma, and so on ( 11 - 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, since this is not viable in a clinical setting, a validated alternative solution is to estimate the IF from the 60-min PET data using an image-derived input function (IDIF) [3,5,11]. Since the acquisition of the initial part of the scan after injection is required, some groups have proposed shorter "dual time-point" protocols [12,13] where the IDIF is obtained from an initial 0-6 min scan over the heart region, and the patient is rescanned again later for example 60-75 min after injection. Although this alternative temporarily frees the scanner for other patients, it is logistically challenging and requires extra CT scans.…”
Section: Introductionmentioning
confidence: 99%